P86 A systematic review of malignant versus benign solitary fibrous tumours of the pleura (SFTP). (December 2018) - Mercer, RM; Wigston, C; Hassan, M; Asciak, R; McCracken, D; Bedawi, E; Hallifax, R; Rahman, NM
Abstract : Background: SFTP are rare tumours arising from mesothelial parenchymal cells. The majority follow a benign course, but these tumours do have the potential to metastasise. England et al developed a set of criteria to define which tumours are malignant including mitotic index, cellularity, pleomorphism, haemorrhage and necrosis. SFTP are heterogenous and a malignant diagnosis can be missed if limited areas are examined, although histologically benign tumours can still follow a malignant course. There is no agreed treatment or management strategy for SFTP – we therefore performed a systematic review of the available literature regarding the diagnosis of benign versus malignant SFTP. Methods: A broad search strategy of four large databases was undertaken for any articles related to SFTP from inception of the database until November 2017. There were no randomised control trials thus large case series were the mainstay of evidence for the systematic review. Data was collected according to a pre-specified protocol and assessed by two reviewers. Results: 21 papers were suitable for data extraction for this question from an initial review of 3447 abstracts. Rates of malignancy ranged from 0% to 57%. The criteria proposed by England et al was used in 14/21 papers with another 4/21 using part of this criteria. 8/21 studies specifically assessed factors which could help differentiate between malignant and benign tumours. 6/8 studies found that large tumours were more likely to be malignant. 3/3 studies showed that the presence of a pleural effusion was associated with malignancy. Non-visceral origin and sessile attachment were not found to have any association in 3/4 studies. There was no association with age and likelihood of a malignant diagnosis. Further associations were reported in solitary papers such as PET avidity, inverted tumours, hypervascularity, lobulated margins and fibrous adherences. Conclusion: Features such as size and the presence of a pleural effusion suggest a SFTP is likely to be histologically malignant. Previous criteria such as sessile attachment and non-visceral origin are not consistently predictive of malignancy. Whilst being able to identify which SFTP are likely to be malignant is important, benign tumours can still follow a malignant course and thus further work is needed to identify all tumours which require a more aggressive management/monitoring strategy.